59 OBTAINING SEXUAL HISTORIES AND SCREENING TEENS FOR CHLAMYDIA: ARE PROVIDERS BIASED?. (1st January 2005) - Tebb, K; Williams, J.; Branch, R.; Goldberg, A.; Pai-Dhungat, M.; Wibbelsman, C.; Shafer, M.
Abstract : Purpose: Fewer than 1/2 of the sexually active young females are being screened annually for C. trachomatis (CT). To address barriers to screening, this study examined gender, ethnicity, and age disparities in adolescents who are screened for CT during regularly scheduled pediatric health checks. Methods: This study was part of a larger randomized controlled trial to increase CT screening among sexually active teens (14-18 years old) during their regularly scheduled health checks in 10 pediatric clinics at a large Northern California health maintenance organization. Teens attending the 5 intervention clinics were asked to complete an anonymous survey at the end of their visit to determine site specific sexual activity rates in order to monitor CT screening rates. The survey gathered basic demographic information on the teens' age, gender, and race/ethnicity. In addition, the survey asked: "Have you ever had sexual intercourse?" and "Did you have a test for STDs today?" Results: There were 4, 368 (49.5% female, 46.4% male and 4.1% did not report gender). The response rate was 74%. The mean age was 15.4 years for females and 15.3 for males. The ethnicity of the overall population was: Asians 26.7%; Blacks 13.2%; Latino19.5%; Caucasian 25.5%; Multi-ethnic/other14.3%. Most teens (83%) were asked about sexual activity; 19.7% had had sex (20.4% for females and 19.0% for males); 7% had an STD test on the day of their visit, 80.1% were not tested for an STD, and 12.5% did not know whether they were tested for an STD. There was no difference in STD screening across gender, ethnicity, or age; yet, there were significant ethnic, age and gender differences in queries about sexual activity. Blacks were significantly more likely to report being asked than Asians (89% vs 81%, p≤0.001) and Latinos (89% vs 81%, p≤0.001). Older teens were more likely to be asked than younger teens (p≤0.05); and female adolescents were more likely than males to be asked about sex (85% vs 83%, p=0.01). Conclusions: Data revealed that there were no differences in who is screened for CT once the sexual history is obtained: however, there are disparities in sexual history taking. While it is encouraging that so many teens were asked about their sexual history, African Americans, older teens, and females were more likely to be asked about sexual history than their counterparts. Providers should be wary of introducing their own bias into screening protocols when universal screening of all sexually active adolescent females is recommended.